Trade Secret Protection as Part of Intellectual Property System: a Comparative Study of Indonesian and United States of America Trade Secret Law - Febrina, Monica Yesica; Manullang, Sardjana Orba (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2020)
Legal protection of intellectual property is an important element in supporting creativity and trade. Indonesia has ratified the Agreement and Trade Related Aspects of Intellectual Property Rights and has enacted Law number 30 of 2000 concerning Trade Secret. Legal protection of trade secrets aims to protect business actors in trade practices both regionally and internationally. In addition, protection of trade secrets can prevent unfair business competition. Thus, business people have wider opportunities to develop their creativity and business. This research method is a normative research with comparative research type. This study examines the comparison of intellectual property protection laws specifically regarding trade secrets with laws in United States. The purpose of this comparative normative study to examine the extent to which the Trade Secret Act can be effective in its application as can be applied in the Supreme Court Decision.